RAYNAUD'S SYNDROME IN CHILDREN - Iskanova G.Kh. (Modern American Journals, 2025)
Buerger's disease, or thromboangiitis obliterans, is a systemic immunopathological inflammatory disease of small and medium-sized vessels of the extremities, in which obliteration of the arteries occurs and migrating thrombophlebitis occurs. The disease mainly affects young people under the age of 40. But according to some sources, this disease occurs in children too. [1,2,3,4,7,8].